2008
DOI: 10.2967/jnumed.108.051920
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Large-Vessel Involvement in Giant Cell Arteritis with 18F-FDG PET: Introducing an ROC-Analysis–Based Cutoff Ratio

Abstract: In the diagnosis of giant cell arteritis (GCA) with aortic involvement, 18 F-FDG PET has been demonstrated to be a powerful tool. No other imaging method is able to directly detect acute inflammation within the aortic wall. However, because GCA is a rare PET indication, the assessment of GCA with 18 F-FDG PET remains difficult and highly dependent on the experience of the investigator. This study aimed to semiquantify the relationship between aortic and liver uptake and to introduce a receiver operating charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(85 citation statements)
references
References 31 publications
1
77
2
5
Order By: Relevance
“…A pattern of high-grade (equal to or higher than liver activity) 18 F-FDG uptake in the vessel wall of the thoracic aorta and/or its major branches (carotid and subclavian arteries) was observed in these patients (Tables 1 and 3, Figure 2). This is in accordance with a recent study which, by applying receiver operator curve analysis in GCA patients and healthy control subjects, calculated an aortic wall/liver 18 F-FDG uptake ratio of .1.00 to be highly sensitive (89%) and specific (95%) for diagnosing vasculitis [12]. In the series of Walter et al [9], who applied a similar scoring system to our study, a vessel score $2 was not found to be sensitive (60%) but still demonstrated high specificity (99%).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A pattern of high-grade (equal to or higher than liver activity) 18 F-FDG uptake in the vessel wall of the thoracic aorta and/or its major branches (carotid and subclavian arteries) was observed in these patients (Tables 1 and 3, Figure 2). This is in accordance with a recent study which, by applying receiver operator curve analysis in GCA patients and healthy control subjects, calculated an aortic wall/liver 18 F-FDG uptake ratio of .1.00 to be highly sensitive (89%) and specific (95%) for diagnosing vasculitis [12]. In the series of Walter et al [9], who applied a similar scoring system to our study, a vessel score $2 was not found to be sensitive (60%) but still demonstrated high specificity (99%).…”
Section: Discussionsupporting
confidence: 66%
“…Yet the accuracy of this technique has not been defined, nor has its exact clinical role been established with respect to initial diagnosis, evaluation of the response to therapy, monitoring of disease activity or follow-up. The 18 F-FDG PET studies that have been performed demonstrate notable variability regarding the diagnostic criteria (visual scoring systems for 18 F-FDG uptake, semi-quantitative standardised uptake values (SUVs) and target to background ratios) [9][10][11][12] used for differentiation between affected and unaffected vessels and for assessment of disease activity.…”
mentioning
confidence: 99%
“…(c) Positive 67 Ga uptake in the heart. 25 In 2006, the joint committee of the Japan Society of Sarcoidosis and Other Granulomatous Disorders, and the Japanese College of Cardiology published a revised version (see Table 1).…”
Section: Major Criteriamentioning
confidence: 99%
“…Currently, conventional angiography is basically used to guide endovascular intervention procedures or to combine imaging with the detection of central blood pressure in patients with significant limb artery stenoses. Systematic evaluation of patients with large-vessel vasculitis with imaging studies such as color duplex ultrasonography (US), CTA, FDG-PET, angiography, and magnetic resonance imaging (MRI) or MR angiography (MRA) has been performed by several investigators (Agard et al, 2008;Andrews et al, 2004;Andrews & Mason, 2007;Blockmans et al, 2008;Blockmans et al, 2009;Both et al, 2008;Hautzel et al, 2008;Henes et al, 2008;Narvaez et al, 2005;Pipitone et al, 2008;Prieto-Gonzalez et al, 2009;Walter et al, 2005;Webb & Al-Nahhas 2006). These techniques offer different but complementary information to assess large vessel involvement with relative advantages and disadvantages which are summarized in Table 3 (Tso E et al, 2002;Blockmans et al, 2009;Cid et al, 2009;).…”
Section: Diagnosis and Assessment Of Aortic Inflammationmentioning
confidence: 99%